2021
DOI: 10.1212/nxi.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Kappa-Free Light Chains in CSF Predict Early Multiple Sclerosis Disease Activity

Abstract: ObjectiveTo investigate whether κ-free light chain (κ-FLC) index predicts multiple sclerosis (MS) disease activity independent of demographics, clinical characteristics, and MRI findings.MethodsPatients with early MS who had CSF and serum sampling at disease onset were followed for 4 years. At baseline, age, sex, type of symptoms, corticosteroid treatment, and number of T2 hyperintense (T2L) and contrast-enhancing T1 lesions (CELs) on MRI were determined. During follow-up, the occurrence of a second clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 47 publications
2
58
0
2
Order By: Relevance
“…Over all studies, the mean prevalence of OCB positivity in MS patients was 94% (min-max: 85-100%) reflecting the importance of detection of intrathecal inflammation as a criterion for dissemination in time [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. Nevertheless, it has to be considered that some studies only included OCB-positive MS patients while other studies comprised a certain percentage of OCB-negative MS patients, thus leading the observed wide range of OCB prevalence [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. KFLC measurements, interpreted by different approaches, reached a mean diagnostic sensitivity of 94% (min-max: 72-100%) and specificity of 84% (min-max: 65-100%) in MS patients [24,…”
Section: The Value Of Kflc As a Csf Biomarker In The Diagnosis Of Msmentioning
confidence: 99%
See 4 more Smart Citations
“…Over all studies, the mean prevalence of OCB positivity in MS patients was 94% (min-max: 85-100%) reflecting the importance of detection of intrathecal inflammation as a criterion for dissemination in time [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. Nevertheless, it has to be considered that some studies only included OCB-positive MS patients while other studies comprised a certain percentage of OCB-negative MS patients, thus leading the observed wide range of OCB prevalence [24,[26][27][28][29]33,[42][43][44]47,48,55,56,[68][69][70][71][72][73][74][75]92]. KFLC measurements, interpreted by different approaches, reached a mean diagnostic sensitivity of 94% (min-max: 72-100%) and specificity of 84% (min-max: 65-100%) in MS patients [24,…”
Section: The Value Of Kflc As a Csf Biomarker In The Diagnosis Of Msmentioning
confidence: 99%
“…The index calculation may be employed for the evaluation of intrathecal synthesis of KFLC as well as for LFLC. Different studies applied KFLC indices varying between 0.92 and 20 and reached a mean diagnostic sensitivity of 87% (82%, 92%) and a mean diagnostic specificity of 87% in MS patients (83%, 91%) [19][20][21][22][23][24][27][28][29]33,42,[44][45][46][47][48][49][50][51]53,54,[56][57][58][59][60][61]64,65,[68][69][70][71][72][73][74][75][78][79][80][81][82]85,87,92]. It has to be considered that in some of these studies, the diagnostic utility of FLC in OCB-negative MS patients was investigated, leading to very low diagnostic sensitivity.…”
Section: Kflc Threshold Values In the Diagnosis Of Msmentioning
confidence: 99%
See 3 more Smart Citations